Penerapan Fungsi Manajemen Peserta Didik Dalam Meningkatkan Mutu Lulusan Di SMPI Yaqin 01 Montong Batu Bawi - Irwan Yon Hadi; Saprudin Efendi Efendi; Wawan Jaya Purnama (Lembaga Pendidikan Al-Gafari, 2023)
In an institution of education existence head of school is one _ aspect important, in addition to teachers, staff employees, facilities and infrastructure, and others. The head school must be capable affect other people and the environment around including the environment school. Study This aim To know How application function management increases the quality of graduates at SMPI Yaqin 01 Montong Batu Bawi because quality growing education from year to year proven with many amount participant pupils and students continuing graduates _ his school by guidance received from SMPI Yaqin 01 Montong Batu Bawi. Study This uses an approach qualitative descriptive. technique data collection used in the study This is interview, observation, and documentation with subject study Head schools, teachers, and students nor society. Research results This shows that management quality graduates from SMPI Yaqin 01 Montong Batu Bawi, got seen efforts made by _ the head school to increase management quality education, and efforts made head school is with method improve the learning process by the demands curriculum and needs of students, improve functions field and management school in a manner construct, improve means Adequate learning, improve quality power education, recruitment after with fields and tasks, improve the welfare of teachers and employees as well as need students, improve quality students, create support public to pseudo active at school, as well increase education insightful religion at school.